The last days of Lilah Goodluck - Scott, Kylie (Graydon House, 2024)
Saving the life of Good Witch Willow, Lilah Goodluck receives five unwanted predictions as a reward, and when the first three predictions come true, she is sent into a panic since, according to the fifth prediction, she only has a week to live unless she can stop the fourth one from happening.